TYROSINE KINASE INHIBITORS AND PREGNANCY - Abruzzese, Elisabetta; Trawinska, Malgorzata Monika; De Fabritiis, Paolo; Perrotti, Alessio Pio (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
The management of patients with chronic myeloid leukemia (CML) during pregnancy has became recently a matter of continuous debate. The introduction of the Tyrosine Kinase Inhibitors (TKIs) in clinical practice has dramatically changed the prognosis of CML patients. Patients diagnosed in chronic phase can reasonably expect many years of excellent disease control and good quality of life, as well as a normal life expectancy. This fact has come the necessity to address issues relating to fertility and pregnancy. Physicians are not infrequently being asked for advice regarding the need for, and or the appropriateness of, stopping treatment in order to conceive. In this report we will review the data published in terms of fertility, conception, pregnancy, pregnancy outcome and illness control for all the approved TKIs, as well as suggest how to manage a planned and/or unplanned pregnancy.